Effectiveness of Garuda Indonesia Self Check-In on Services and Operations at Soekarno-Hatta International Airport - Salsabilla Haura Friskasari; Brendha Chintya Conny; Dinar Dewi Kania (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The self check-in process remains a challenge for elderly passengers due to their unfamiliarity with technology. This study aims to evaluate the effectiveness of self check-in services and operations at Soekarno-Hatta International Airport. Using a descriptive qualitative method and interviews as the primary data collection technique, the findings revealed that PT. Gapura Angkasa (Garuda Indonesia) collaborates with several vendors to offer self check-in. These self check-in employ techniques such as entering booking numbers, ticket numbers, and passport scans. A major drawback identified is the potential misuse of booking numbers or tickets, although identity verification is conducted at the boarding gate. The self check-in provide bilingual options in Indonesian and English to enhance usability. However, passengers unfamiliar with technology, particularly the elderly, may still encounter difficulties. To prevent long queues, check-in staff are available to assist passengers.